Automação de um sistema de coleta de leite cru a granel - Elias, Matheus Casa Santo (2021)
The process of transporting quality milk to people's tables is still far from ideal, whether in Brazil or in the rest of the world. The great increase in production and consumption worldwide, together with increasingly strict quality standards, bring the need for new technologies and improvement of processes in the dairy production chain. These, however, are largely focused on production and processing, leaving a large gap in the process of collecting and transferring this material to the dairy, where there are still many manual processes, susceptible to errors and fraud. Thus, this project arises, with support from the Parque Tecnológico Itaipú, for the development of an embedded system of a device that automates the measuring of milk volume and temperature during collection. In addition, there is the application of the Modbus communication protocol in the Bluetooth and USB connections, which, in addiction to make the system at an industrial level, allows the acquisition of collection data automatically, eliminating the chance of human error and fraud at this stage of the process, which brings reliability, security and transparency. For better milk traceability, the system also has the ability to store a history with a capacity of up to 125 collections.